Pemena: Toward a Relational Ecophilosophy of Health Among the Karo People of North Sumatra - Ginting, Johannes Bastira; Suci, Tri; Ginting, Chrismis Novalinda; Indriyanto, Kristiawan (Studia Ecologiae et Bioethicae, 2026)
This article examines Pemena, the traditional belief system of the Karo people of North Sumatra, as a relational ecophilosophy of health. Pemena—meaning “the first”—defines health not as individual biological function but as balanced relationships among humans, ancestral spirits (begu), guardian spirits (nini), and vital essence (tondi). We analyze healing practices, including Erpangir Ku Lau (purification at sacred springs) and the authority of guru sibaso (ritual healers) to demonstrate how Pemena treats illness as rupture within cosmic relationships requiring spiritual, ecological, and social repair simultaneously. This ontology challenges biomedical reductionism's focus on isolated pathology and Western ecophilosophy's secular rationalism. Pemena recognizes nonhuman agents—springs, forests, ancestral forces—as active participants in health decisions through ritual negotiation. While scholars often categorize such systems as Traditional Ecological Knowledge (TEK), Pemena constitutes a distinct philosophical tradition requiring engagement on its own terms. Existing scholarship catalogs Karo medicinal plants but ignores the cosmological structures making these practices coherent. We examine how Indonesian health policy (Law 36/2009) marginalizes Pemena by conditioning legitimacy on biomedical validation, arguing that genuine health pluralism requires legal frameworks accommodating different healing ontologies rather than forcing Indigenous systems into external categories.